Extreme clonality in lymphoblastoid cell lines with implications for allele specific expression analyses. - Vincent Plagnol; Elif Uz; Chris Wallace; Helen Stevens; David Clayton; Tayfun Ozcelik; John A Todd (PLoS ONE)
Lymphoblastoid cell lines (LCL) are being actively and extensively used to examine the expression of specific genes and genome-wide expression profiles, including allele specific expression assays. However, it has recently been shown that approximately 10% of human genes exhibit random patterns of monoallelic expression within single clones of LCLs. Consequently allelic imbalance studies could be significantly compromised if bulk populations of donor cells are clonal, or near clonal. Here, using X chromosome inactivation as a readout, we confirm and quantify widespread near monoclonality in two independent sets of cell lines. Consequently, we recommend where possible the use of bulk, non cell line, ex vivo cells for allele specific expression assays.